Metabolomics New Insights into Biology and Medicine - Hozzein, Wael N. (Biochemistry, 2020)
This book is mainly for researchers interested in the new developments and applications of metabolomics. It is also important for physicians using metabolomic approaches in the diagnosis of diseases or treatment, and for postgraduate students starting their research projects on metabolomics. The book is divided into two sections as indicated from its title, namely: new insights into biology and new insights into medicine. It gives examples of the different applications of metabolomics from the production of biosurfactants by marine microorganisms to the applications of data from fecal metabolomics, serum metabolomics, and metabolomics of microbiota, as well as the use of Chinese medicines for cancer treatment. Overall, this is a well-written book, containing some very interesting research avenues and cutting-edge approaches. Finally, the editing of this book was of special interest to me and I hope that readers will also find it stimulating.